Concurrent optical absorption and viscosity characterization using pulsed photoacoustic - Lee, Chunwei (2015)
Photoacoustic imaging allows for spatial detection of strongly absorbing exogenous contrast agents, such as blood. These contrast agents facilitate the detection of cellular and molecular events and can distinguish diseased from normal tissues. This provides an opportunity for image-guided clinical applications such as cancer detection, diagnosis and therapy guidance.[6] Although the photoacoustic method has made great progress in the past decade, there are few achievements that can simultaneous obtaining two parameters to eventually provide comprehensive information for pathological diagnosis. In this report, we will first understand some basic background concept and working principle of photoacoustic. Next, study a few Kwave Toolbox simulations provided by Matlab software. Follow by, a stimulation using single pulse wave to determine alpha coefficient and disc magnitude in an ideal and practical cases. Lastly, an experimental setup of photoacoustic measurement. The amplitude of a photoacoustic signal (Disc Magnitude) is proportional to the optical absorption of the tissues. The contrast of the imaging is determined by different optical absorption of different tissues. From the stimulation, the Disc Magnitude only influence by Peak to Peak values. As for viscoelasticity, we will be studying more on viscosity rather than the elastic characteristics. Through the Equation (16), Alpha Coefficient is proportional to viscosity and can be changed with Peak to Peak and Peak Ratio values. Therefore, Alpha Coefficient should be determined first. Follow by, compute the attenuation losses. The final step will be computing Disc Magnitude and multiplying with attenuation ratio. Detailed calculation and explanations will be cover in the later part of this report.